Astronomical Photometry Past, Present, and Future - Milone, Eugene F.; Sterken, C.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
This book brings together experts in the field of astronomical photometry to discuss how their subfields provide the precision and accuracy in astronomical energy flux measurements that are needed to permit tests of astrophysical theories. Differential photometers and photometry, improvements in infrared precision, the improvements in precision and accuracy of CCD photometry, the absolute calibration of flux, the development of the Johnson UBVRI photometric system and other passband systems to measure and precisely classify specific types of stars and astrophysical quantities, and the current capabilities of spectrophotometry and polarimetry to provide precise and accurate data, are all discussed in this volume. The discussion of `differential$1 (Bor `two-star$1 (Bphotometers ranges from early experiments in visual photometry through the Harvard and Princeton polarizing photometers to the pioneering work of Walraven and differential photometers designed to minimize effects of atmospheric extinction and to counter the effects of aurorae at high latitude sites; two of these are the Pierce-Blitzstein photometer of the University of Pennsylvania, in use for several decades, and the Rapid Alternate Detection System (RADS) developed at the University of Calgary in the 1980s.s
Photometric Precision and Accuracy -- The High Road to Astronomical Photometric Precision: Differential Photometry -- High Precision Differential Photometry with CCDs: A Brief History -- The Pierce-Blitzstein Photometer -- Johnson Photometry and its Descendants -- The Rise and Improvement of Infrared Photometry -- On the Use of Photometry in Spectral Classification -- Absolute Photometry: Past and Present -- Optical Region Spectrophotometry: Past and Present -- Measurement of Polarized Light in Astronomy -- Index -- References.
Keywords: Physics; Physics; Astrophysics and Astroparticles; Signal, Image and Speech Processing; Measurement Science and Instrumentation